Insulin and Memory in Invertebrates - Nakai, Junko; Chikamoto, Nozomi; Fujimoto, Kanta; Totani, Yuki; Hatakeyama, Dai; Dyakonova, Varvara E.; Ito, Etsuro (Frontiers in Behavioral Neuroscience, 2022)
Insulin and insulin-like peptides (ILP) help to maintain glucose homeostasis, whereas insulin-like growth factor (IGF) promotes growth and differentiation of cells in both vertebrates and invertebrates. It is sometimes difficult to distinguish between ILP and IGF in invertebrates, however, because in some cases ILP has the same function as IGF. In the present review, therefore, we refer to these peptides as ILP/IGF signaling (IIS) in invertebrates, and discuss the role of IIS in memory formation after classical conditioning in invertebrates. In the arthropod Drosophila melanogaster, IIS is involved in aversive olfactory memory, and in the nematode Caenorhabditis elegans, IIS controls appetitive/aversive response to NaCl depending on the duration of starvation. In the mollusc Lymnaea stagnalis, IIS has a critical role in conditioned taste aversion. Insulin in mammals is also known to play an important role in cognitive function, and many studies in humans have focused on insulin as a potential treatment for Alzheimer’s disease. Although analyses of tissue and cellular levels have been progressed in mammals, the molecular mechanisms, such as transcriptional and translational levels, of IIS function in cognition have far advanced in studies using invertebrates. We anticipate that the present review will help to pave the way for studying the effects of insulin, ILPs and IGFs in cognitive function across phyla.